2013
DOI: 10.1136/vetreccr.165.24.718rep
|View full text |Cite
|
Sign up to set email alerts
|

Four cases of omental herniation in cattle

Abstract: Four cases in cattle of omental herniation through an acquired omental rent are described. Clinical signs were indistinguishable from other causes of mechanical ileus and exploratory laparotomy was necessary to establish a diagnosis. In all cases a variably sized portion of jejunal loops was obstructed in an omental rent in the deep layer of the greater omentum. In two cases simple reduction was possible, and in one case incision of the hernial ring was necessary before reduction could be performed. Resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…Omental hernia where a piece of intestine was found prolapsed and entrapped medial to abdominal wall through a local tear of omentum (Pardon et al, 2009;Ruf-Ritz et al, 2013). This entrapment consequently disturbs the intestinal motility and compresses the intestine leading to distension of affected loops (5±0.5 cm diameter) mostly at right abdominal wall (Pardon et al, 2009) that were also demonstrated herein by ultrasonography and then confirmed by necropsy. Another recorded affection in this study is OFN (or abdominal/omental lipomatosis) was successfully diagnosed.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 59%
See 4 more Smart Citations
“…Omental hernia where a piece of intestine was found prolapsed and entrapped medial to abdominal wall through a local tear of omentum (Pardon et al, 2009;Ruf-Ritz et al, 2013). This entrapment consequently disturbs the intestinal motility and compresses the intestine leading to distension of affected loops (5±0.5 cm diameter) mostly at right abdominal wall (Pardon et al, 2009) that were also demonstrated herein by ultrasonography and then confirmed by necropsy. Another recorded affection in this study is OFN (or abdominal/omental lipomatosis) was successfully diagnosed.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 59%
“…Additionally, most of such cases are ultimately referred to the hospital for addressing the problem by an expert sonographer. Thus, as previously reported, ultrasonographic examination of the abdomen plays a central role in diagnosis of internal abdominal abscesses (Abdelaal et al, 2017), diaphragmatic hernia (Abdelaal et al, 2014) and omental hernia (Pardon et al, 2009)…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations